THE IMPORTANCE OF NEW MATERIALS DEVELOPMENT FOR INCREASING GAS TURBINES EFFICIENCY - Souza, F. A.; Bastos, F. M.; Jorge, P. R. M. (Revista de Engenharia Térmica, 2004)
This study shows the effects of new materials for gas turbines and techniques for blade coating. The implication on temperature limits of combustion chambers and consequently on high efficiency is also analyzed.